2015
DOI: 10.1007/s00264-015-2685-y
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative treatment in osteochondral lesions of the talus: autologous chondrocyte implantation versus one-step bone marrow derived cells transplantation

Abstract: To date, ACI and BMDCT showed to be effective regenerative techniques for the treatment of OLT. BMDCT could be preferred over ACI for the single step procedure, patients' discomfort and lower costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 26 publications
2
88
0
4
Order By: Relevance
“…At the final follow-up, 72.8% were able to resume sports at preinjury level. Buda et al [52] compared clinical outcomes of two clusters of patients who underwent ACI or BMDCT for OLT and demonstrated that clinical results were similar in both groups at 48 months of follow-up. The rate of return to sports activity showed slightly better results for BMDCT compared to ACI; however, the difference was not statistically significant.…”
Section: Bone Marrow-derived Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the final follow-up, 72.8% were able to resume sports at preinjury level. Buda et al [52] compared clinical outcomes of two clusters of patients who underwent ACI or BMDCT for OLT and demonstrated that clinical results were similar in both groups at 48 months of follow-up. The rate of return to sports activity showed slightly better results for BMDCT compared to ACI; however, the difference was not statistically significant.…”
Section: Bone Marrow-derived Cell Transplantationmentioning
confidence: 99%
“…Several clinical studies have shown that clinical outcomes improved using this procedure [49][50][51][52][53]54•]. Giannini et al [53] evaluated patients who underwent BMDCT and demonstrated improved AOFAS scores from 63.7 to 82.2 in 49 patients at a mean follow-up of 48 months.…”
Section: Bone Marrow-derived Cell Transplantationmentioning
confidence: 99%
“…1,11,[14][15][16] Previously published series showed encouraging results on general population; still no exhaustive articles report the results of this technique on the athletes and its impact on the return to sports. 1,11,[14][15][16] The aim of this study was to evaluate the return to sport of athletes with OLT, treated with one-step BMDCT procedure.…”
Section: Introductionmentioning
confidence: 99%
“…11 Nevertheless, microfractures restore a fibrocartilage tissue; whereas other techniques like autologous chondrocyte implantation (ACI) or bone marrow-derived cell transplantation (BMDCT) regenerate good quality hyaline cartilage. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] These techniques imply a longer rehabilitation (12 months): moreover, ACI requires high costs and 2 operations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation